2005
DOI: 10.1029/2004gl021497
|View full text |Cite
|
Sign up to set email alerts
|

Solar control on Jupiter's equatorial X‐ray emissions: 26–29 November 2003 XMM‐Newton observation

Abstract: [1] During Nov. [26][27][28][29] 2003 XMM-Newton observed soft (0.2 -2 keV) X-ray emission from Jupiter for 69 hours. The low-latitude X-ray disk emission of Jupiter is observed to be almost uniform in intensity with brightness that is consistent with a solar-photon driven process. The simultaneous light curves of Jovian equatorial X rays and solar X rays (measured by the TIMED/SEE and GOES satellites) show similar day-to-day variability. A large solar X-ray flare occurring on the Jupiter-facing side of the S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 13 publications
3
62
0
Order By: Relevance
“…Jupiter's equatorial emissions are produced by solar photons that are fluoresced and scattered in Jupiter's atmosphere 38,40,41 . Lightcurves and PSDs from the Jovian equator on 24 May (DoY 145) and 1 June (DoY 153) (Supplementary figure 4) between -30° and 30° latitude demonstrate that the periodic behaviour is not present in the equatorial region and that there was not a significant variation in the solar X-ray output (e.g.…”
Section: Lightcurves and Xmm-newton Periodicity Detectionmentioning
confidence: 99%
“…Jupiter's equatorial emissions are produced by solar photons that are fluoresced and scattered in Jupiter's atmosphere 38,40,41 . Lightcurves and PSDs from the Jovian equator on 24 May (DoY 145) and 1 June (DoY 153) (Supplementary figure 4) between -30° and 30° latitude demonstrate that the periodic behaviour is not present in the equatorial region and that there was not a significant variation in the solar X-ray output (e.g.…”
Section: Lightcurves and Xmm-newton Periodicity Detectionmentioning
confidence: 99%
“…Elastic and fluorescent scattering of solar X-rays takes place in planetary atmospheres (and on moon surfaces), in such a way that the planetary disks are seen to mirror the solar X-ray variability, on short timescales and over the solar cycle (e.g. Bhardwaj et al 2005b;Branduardi-Raymont et al 2010).…”
Section: X-ray Emission Processesmentioning
confidence: 99%
“…Branduardi-Raymont et al 2004, 2007b, 2008Bhardwaj et al 2005b). They showed that the equatorial component is predominantly caused by scattered solar X-rays (Maurellis et al 2000;Bhardwaj et al 2005b;Branduardi-Raymont et al 2007b), similar to Venus and Mars, and indicated that charge exchange is the basic explanation of the polar component for X-ray energies below ∼ 2 keV, while bremsstrahlung of energetic electrons precipitating from the magnetosphere may be responsible for the X-ray emission at higher energies (Branduardi-Raymont et al 2004, 2007a, 2008. In contrast to the nonmagnetic planets, however, where the heavy ions are supplied by the solar wind, the heavy ions could also originate from the Jovian magnetosphere, by acceleration and subsequent additional ionization of ambient sulfur and oxygen ions in a field-aligned potential (Bunce et al 2004), as explored by , who considered the second possibility more likely.…”
Section: Magnetic Planets With Atmospheresmentioning
confidence: 99%